Pengaruh Indeks Pembangunan Manusia (IPM), Produk Domestik Regional Bruto (PDRB) terhadap Kemiskinan melalui Pertumbuhan Ekonomi di Provinsi Sulawesi Selatan - Anwar Ramli; Anwar Anwar; Yusri Karmila (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Overcoming poverty is a major challenge for the government to improve the standard of living of the population by immediately finding solutions to reduce poverty. The objectives of the study are: 1) to determine the Effect of the Human Development Index (HDI) on Poverty in South Sulawesi Province; 2) to determine the Effect of Gross Regional Domestic Product (GRDP) on Poverty in South Sulawesi Province; 3) to determine the Effect of the Human Development Index (HDI) on Poverty through economic growth in South Sulawesi Province; 4) to determine the Effect of Gross Regional Domestic Product (GRDP) on Poverty through economic growth in South Sulawesi Province. The research method is quantitative analysis used in this study, namely a method carried out through numerical measurements using statistical methods. The approach used is the Structural Equation Modeling (SEM) method in quantitative research. Research method stage. Based on the results of the analysis and discussion of research related to the effect of HDI, GRDP, and Economic Growth (PE) on poverty, there are several important points that can be concluded. First, HDI has no direct or indirect effect on poverty. Second, GRDP does not show a direct effect on poverty. Third, economic growth has been shown to act as a full mediator in the relationship between GRDP and poverty. Conversely, economic growth is unable to mediate the relationship between the HDI and poverty, so the mechanism by which human development-related variables influence poverty reduction is not yet optimal. This research emphasizes the importance of inclusive economic growth so that the benefits of development can be felt by all levels of society, especially the poor. Increasing GRDP and HDI needs to be integrated with economic policies that encourage expanded employment opportunities and equitable economic access to make a real contribution to poverty reduction.